2018
DOI: 10.1016/j.cyto.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic inflammation by hyaluronan and hsp70 in women with pre-eclampsia

Abstract: Pre-eclampsia (PE) is a human pregnancy syndrome with abnormal activation of the innate immune response. The study evaluated the involvement of molecular structures called damage-associated molecular patterns (DAMPs), such as hyaluronan (HA) and heat shock proteins (Hsp) on NLRP1 and NLRP3 inflammasomes activation in peripheral blood monocytes. Twenty pre-eclamptic women, 20 normotensive pregnant women (NT) and 20 non-pregnant women (NP) were studied. Enzyme immunoassay was employed for the determination of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The results of the present study show that monocytes from preeclamptic women are endogenously activated and may play a role in the systemic inflammatory response already described in PE [26,27]. Compared with NT pregnant women, basal gene expression of NLRP1 and NLRP3 inflammasomes, the TLR4/NF-κB pathway and pro-inflammatory cytokines were significantly increased in monocytes from preeclamptic women, findings that highlight the inflammatory profile of these cells.…”
Section: Discussionsupporting
confidence: 71%
“…The results of the present study show that monocytes from preeclamptic women are endogenously activated and may play a role in the systemic inflammatory response already described in PE [26,27]. Compared with NT pregnant women, basal gene expression of NLRP1 and NLRP3 inflammasomes, the TLR4/NF-κB pathway and pro-inflammatory cytokines were significantly increased in monocytes from preeclamptic women, findings that highlight the inflammatory profile of these cells.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, this effect was abolished by glibenclamide, an NLRP3 inhibitor [ 45 ]. Another, similarly designed, study confirmed that NLRP3 is activated by cholesterol, ROS, MSU, hyaluronan, and high glucose concentrations [ 45 , 46 , 47 , 48 , 49 ]. These findings led to the creation of the NLRP3 crystal-induced activation theory, where MSU, alum, silica, asbestos, β-amyloid, cholesterol crystals, and calcium crystals, induces NLRP3 inflammasome activation [ 6 , 45 ].…”
Section: Nlrp3 Activators In Pe and Pihmentioning
confidence: 87%
“…Excessive inflammation causes placental damage, placental development abnormalities, systemic endothelial system activation, and lease of antiangiogenic factors and thus leads to preeclampsia (Cornelius, 2018;I et al, 2017;Romao-Veiga et al, 2018). Accumulated data have Sakai, & Sasaki, 2007).…”
Section: Discussionmentioning
confidence: 99%